2021
DOI: 10.3390/jmse9111303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Database Generation on Damage Consequences’ Assessment Based on Random Forests

Abstract: Recently, the application of machine learning has been explored to assess the main damage consequences without employing flooding sensors. This method can be the base of a new generation of onboard decision support systems to help the master during the progressive flooding of the ship. In particular, the application of random forests has been found suitable to assess the final fate of the ship and the damaged compartments’ set and estimate the time-to-flood. Random forests have to be trained using a database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Other studies have introduced hybrid or multi-level real-time flooding risk evaluation [124]. Furthermore, recent studies have shown the potential for the application of data-driven techniques to the problem based on pre-calculated progressive flooding simulations [125][126][127][128][129].…”
Section: Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have introduced hybrid or multi-level real-time flooding risk evaluation [124]. Furthermore, recent studies have shown the potential for the application of data-driven techniques to the problem based on pre-calculated progressive flooding simulations [125][126][127][128][129].…”
Section: Predictionmentioning
confidence: 99%
“…Likewise, Braidotti et al [128,129] have developed promising machine learning-based flooding progression methodologies.…”
Section: Identification Prediction and Responsementioning
confidence: 99%
“…The paper written by Braidotti et al [1] is related to the unsinkability problem; however, their scope is far beyond the classic single-case formulations. First, a scenario of the schematised accidental lateral ramming was considered and used for the generation of a damages database.…”
Section: Contributions' Overviewmentioning
confidence: 99%
“…A progressive flood simulation was employed using a database-trained machine learning algorithm to assess the main consequences of a damage scenario. Furthermore, the application of random forests was proved to be suitable for assessing the final state of ships and damaged compartment settings and estimating flooding time [30].…”
Section: Introductionmentioning
confidence: 99%